1999
DOI: 10.1542/peds.104.4.e50
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Patterns in Relation to Thumb Sucking and Pacifier Use

Abstract: More frequent use of a pacifier was associated with shorter breastfeeding duration, even among a group of mothers who were highly motivated to breastfeed. breastfeeding duration, breastfeeding pattern, exclusive breastfeeding, pacifier use, thumb sucking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
82
0
25

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(119 citation statements)
references
References 17 publications
11
82
0
25
Order By: Relevance
“…12 The increased risk was similarly small (approximately 1.5) in the United States, 13 and no impact on early weaning was found in Canada. 14 In southern Brazil, however, a marked effect on the risk of shortened duration was found with a hazard ratio of 3 associated with pacifier use at 1 month.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…12 The increased risk was similarly small (approximately 1.5) in the United States, 13 and no impact on early weaning was found in Canada. 14 In southern Brazil, however, a marked effect on the risk of shortened duration was found with a hazard ratio of 3 associated with pacifier use at 1 month.…”
Section: Discussionmentioning
confidence: 94%
“…In Sweden, however, there has been a declining trend in pacifier use in the first week of life, and there was a sudden drop in 1992 (from 57% to 36%) coincident with the launch of the Baby Friendly Hospital Initiative. 12 In Brazil, a more achievable short-term goal may be to delay their introduction. Formative research is needed to identify approaches and motivational messages for achieving such a goal.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, early use of a pacifier and/or feeding bottle may cause some infants to adopt a faulty breastfeeding technique, the so-called nipple confusion, which may lead to early weaning. 9,[11][12][13][14] Some studies suggested a relationship between pacifier use, as well as bottle-feeding, and bacteria or yeast infections, chiefly Candida albicans. 9,12 Moreover, pacifier use has also been implicated in an increased risk for acute otitis media.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] A direct relationship between short breastfeeding duration and increased prevalence of non-nutritive sucking habits, especially pacifier use, has been reported. [8][9][10][11][12][13][14][15] However, a possible association between breast-or bottle-feeding durations and the age of persistence of pacifier-sucking habits is not completely elucidated. Information on the age at which prolonged non-nutritive sucking behaviors cease would be more meaningful to better understand the etiology of malocclusions in the primary dentition than a simple positive registration of such habits.…”
Section: Introductionmentioning
confidence: 99%
“…A negative correlation between the use of a dummy and successful breastfeeding was found in all 14 studies 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47 published between 1999 and 2012 (Table 3). …”
Section: Resultsmentioning
confidence: 90%